Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/13880209.2020.1762668
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive constituents of Salvia przewalskii and the molecular mechanism of its antihypoxia effects determined using quantitative proteomics

Abstract: Context: Environmental hypobaric hypoxia induces several physiological or pathological responses in individuals in high-altitude regions. Salvia przewalskii Maxim (Labiatae) (SPM) is a traditional Chinese herbal medicine and has known antibacterial, antiviral, antioxidant, anti-thrombotic, and anti-depressant activities. Objective: This study examined the antihypoxia effects of SPM in vivo. Materials and methods: The dried and pulverised of SPM was extracted from root crude drug with 70% ethanol with ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…The roots of S. przewalskii were traditionally used as a folk medicine to achieve the therapeutic effects of enhancing blood circulation, remediating blood stasis, regulating menstruation, and relieving pain [3]. According to the Chinese Materia Medica, the roots of S. przewalskii were prescribed as a surrogate for Danshen (roots of S. miltiorrhiza), a well-known traditional Chinese medicine (TCM) used for the treatment of various cardiovascular diseases [4]. The secondary metabolites from S. przewalskii therefore attracted great interest towards their phytochemical investigation in recent decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roots of S. przewalskii were traditionally used as a folk medicine to achieve the therapeutic effects of enhancing blood circulation, remediating blood stasis, regulating menstruation, and relieving pain [3]. According to the Chinese Materia Medica, the roots of S. przewalskii were prescribed as a surrogate for Danshen (roots of S. miltiorrhiza), a well-known traditional Chinese medicine (TCM) used for the treatment of various cardiovascular diseases [4]. The secondary metabolites from S. przewalskii therefore attracted great interest towards their phytochemical investigation in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, abietane-type diterpenoids and phenolic acid derivatives are two major chemical constituents of the roots of S. przewalskii, which also appears in the phytological related S. miltiorrhiza [5][6][7][8][9][10]. Pharmacological studies revealed the beneficial effects of both the crude extracts and chemical constituents of S. przewalskii, including heart-protective, antioxidative, anti-inflammatory, antitussive, and antibacterial properties [4,[11][12][13][14]. This research not only provided convincing evidence to support the traditional therapeutic effects of this species, but has also provided a comprehensive perspective of further potential medicinal applications.…”
Section: Introductionmentioning
confidence: 99%